Enhancing Security in Industrial IoT: Authentication Solutions Leveraging Blockchain Technology - Rebecca Ling Ze Siew; Brendan Chan Kah Le; Lee Kai Yue; Nuri Nazirah Binti Ismail; Xavier Liong Zhi Hao; Muhammad Faisal (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
The rapid advancement of Industrial Internet of Things (IIoT) technology necessitates robust authentication solutions to ensure security, scalability, and efficiency. This project, titled